Potential Fungi Isolated From Anti-biodegradable Chinese Medicine Residue to Degrade Lignocellulose - Cheng, Min; Wijayawardene, Nalin N.; Promputtha, Itthayakorn; de Vries, Ronald P.; Lan, Yongzhe; Luo, Gang; Wang, Meizhu; Li, Qirui; Guo, Xinyao; Wang, Feng; Liu, Yanxia; Kang, Yingqian (Frontiers in Microbiology, 2022)
Traditional Chinese medicine is one of the ancient medicines which is popular in Asian countries, among which the residue produced by the use of anti-biodegradable is countless, it causes significant adverse impacts on the environment. However, the high acidity of anti-biodegradable residues and some special biological activities make it difficult for microorganisms to survive, resulting in a very low degradation rate of lignocellulose in naturally stacked residues, which directly impedes the degradation of residues. We aimed to identify the fungal strains that efficiently biodegrade anti-biodegradable residue and see the possibility to improve biodegradation of it and other agricultural wastes by co-cultivating these fungi. We isolated 302 fungal strains from anti-biodegradable residue to test hydrolysis ability. Finally, we found Coniochaeta sp., Fomitopsis sp., Nemania sp., Talaromyces sp., Phaeophlebiopsis sp. which inhabit anti-biodegradable residue are capable of producing higher concentrations of extracellular enzymes. Synergistic fungal combinations (viz., Fomitopsis sp. + Phaeophlebiopsis sp.; Talaromyces sp. + Coniochaeta sp. + Fomitopsis sp.; Talaromyces sp. + Fomitopsis sp. + Piloderma sp. and Talaromyces sp. + Nemania sp. + Piloderma sp.) have better overall degradation effect on lignocellulose. Therefore, these fungi and their combinations have strong potential to be further developed for bioremediation and biological enzyme industrial production.